The Effect of Disclosure on Sustainability Reporting, Company Size, Profitability and Leverage on The Value of Companies Included in The LQ45 Index For 2020-2022 - Gusniadi, Revi Ilham; Rita Friyani; Fredy Olimsar (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to empirically prove the influence of sustainability report disclosure, company size, profitability and leverage on company value. This research is quantitative research using secondary data obtained from the company's annual report and the company's sustainability reporting report. The population in this study are companies that are members of the LQ45 index from 2020-2022. The number of samples used in this research was 51 data. The data analysis technique used is multiple linear regression analysis with the software used for data processing is SPSS version 25. Based on the results of the analysis it is known that simultaneously the sustainability report disclosure variables, company size, profitability and leverage influence company value, while partially the variables Sustainability report disclosure, company size, profitability and leverage have a significant effect on company value